Design and Synthesis of Out/Out, Out/In, and In/In Epoxides in Polycyclic Cage Frameworks - Kotha, Sambasivarao; Salman, Mohammad (Synlett, 2024)
We report a useful synthetic approach to assemble in/in epoxide, in/out epoxide, and out/out epoxide in cage systems using the Corey–Chaykovsky reaction and the Peterson olefination as key steps. In this regard, a variety of pentacycloundecane (PCUD) based cage compounds containing oxirane rings with diverse stereochemical disposition were synthesized via a simple synthetic sequence. Five cage diones were used for this purpose, and the starting cage diones were prepared with easily accessible starting materials such as 1,4-hydroquinone derivatives and cyclopentadiene. Here, we have used the Diels–Alder (DA) reaction, a [2+2] photocycloaddition, the Corey–Chaykovsky reaction, and the Peterson olefination as crucial steps to prepare the target molecules.
Keywords: Diels–Alder reaction; photocycloaddition; cage compounds; PCUD; Peterson olefination; Corey–Chaykovsky reaction; m-CPBA oxidation